Community Empowerment In Establishing Entrepreneurial Behavior (Case Study At Pkbm Bina Mandiri Cimahi City And Pkbm Bina Warga Bandung District) - Apandi, Syaban; Wasliman, Iim; fiah, Hana; wati, Helma (CV. Inara, 2022)
This research is generally to find out about community empowerment in establishing entrepreneurial behavior in PKBM Bina Mandiri Cipageran, Cimahi City and PKBM Bina Warga Ciparay, Bandung Regency. Specifically, it is to know the stages of community empowerment, including: (1) preparation stage,(2) assessment stage, (3) alternative program planning stage, (4) action plan formulation stage, (5) implementation stage, (6) stage evaluation and monitoring, and (7) the termination stage. The method used is a descriptive method with qualitative data types. Data was collected through observation, interviews, and documentation studies. The results of the study indicate that in general both PKBM have empowered the community as the target community quite effectively, being more empowered, both cognitively, affectively, psychomotorically and independently with their entrepreneurial behavior. Specifically, the stages of empowerment are in accordance with the stages, including: (1) preparations carried out by preparing officers and field preparations; (2) assessment, namely by identifying the problems of the target community that have the potential to become learning citizens; (3) planning alternative programs, namely facilitating learning residents in determining the right choice of learning programs to overcome problems; (4) formulation of action plans, namely by determining learning times, recruiting target communities, providing program information; (5) implementation, namely program implementation, which begins with socialization, implementation, identification of results, supporting and inhibiting factors, their contribution to the formation of entrepreneurial behavior and their impact on increasing income and welfare; (6) evaluation, through program evaluation and monitoring; and (7) termination or continuation of the program, namely by providing guidance and assistance to learning residents who have completed the Business Study Group program. These stages have been carried out by the two PKBMs in the implementation of learning programs and community empowerment in shaping entrepreneurial behavior.